2015
DOI: 10.1371/journal.pone.0118772
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Death from Influenza A(H1N1)pdm09, State of São Paulo, Brazil, 2009

Abstract: This case-control study aimed to assess the risk factors for death from influenza A(H1N1)pdm09 in patients with laboratory confirmation, who had severe acute respiratory illness-SARI and were hospitalized between June 28th and August 29th 2009, in the metropolitan regions of São Paulo and Campinas, Brazil. Medical charts of all the 193 patients who died (cases) and the 386 randomly selected patients who recovered (controls) were investigated in 177 hospitals. Household interviews were conducted with those who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
2
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 28 publications
3
23
2
5
Order By: Relevance
“…In the review of studies that provided estimates adjusted for the presence of other factors known to impact the risk of severe outcomes for people ill with influenza, we found that the risk estimate was heterogeneous and not consistently greater or less than the pRR estimated with this meta‐analysis …”
Section: Resultsmentioning
confidence: 78%
“…In the review of studies that provided estimates adjusted for the presence of other factors known to impact the risk of severe outcomes for people ill with influenza, we found that the risk estimate was heterogeneous and not consistently greater or less than the pRR estimated with this meta‐analysis …”
Section: Resultsmentioning
confidence: 78%
“…[75][76][77][78][79] During influenza season, obese persons are at increased risk for hospitalization due to respiratory illness and were overrepresented among influenza-associated hospitalizations and deaths the 2009 pandemic. [80][81][82][83] Individuals with diabetes have higher blood and ALS glucose levels correlated with increased respiratory infections ( Table 1). These underlying conditions also associate with hyperglycemia, increased adipose tissue, and chronic inflammation.…”
Section: Clinical and In Vivo Studies Of Iav Metabolismmentioning
confidence: 99%
“…On the one hand, the link between influenza A infection and HPS is relatively new, making it a difficult diagnosis due to the low index of suspicion and explaining why many cases have been identified postmortem [15]. On the other hand, hematological abnormalities (cytopenias) are frequently associated with influenza A infection (especially lymphopenia and trombocytopenia) [16,17] although they tend to be mild in most patients and are generally not associated with a poor prognosis. Therefore, diagnosis of HPS is easily missed if there is no clinical suspicion that takes the treating physician to order specific disease markers as proposed by HLA-04 [2].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, treatment was never started in many cases because of delayed diagnosis. In the study by Beutel et al [14], the median time from the onset of symptoms to the diagnosis of VAHS was 23 days (interquartile range [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. This could explain, at least in part, the poor prognosis of HPS secondary to influenza A infection.…”
Section: Comorbidities/ Co-morbid Infectionsmentioning
confidence: 99%